Prescription and Effects of Strength Training in Individuals with Intellectual Disability-A Systematic Review - Miguel Jacinto; Rafael Oliveira; João P. Brito; Alexandre D. Martins; Rui Matos; José Pedro Ferreira (MDPI AG, 2021)
The practice of physical exercise (PE), especially strength training (ST), has health benefits in the healthy population; however, the literature is scarce in the recommendations related to the population with intellectual disability (ID). This study represents the first analysis on the topic and aims to examine the structure and efficacy of ST experimental intervention programs in individuals with ID. This systematic review was carried out between January and April 2021, using the PubMed, Web of Science, Scopus, and SPORTDiscus databases, according to the PRISMA guidelines. From a total of 166 studies, eight were included in the present systematic review. The studies included a total of 280 individuals (18.23 ± 2.86 years old). The main features of the exercise programs are: 12 weeks average duration, three weekly sessions of 45-60 min, six to seven exercises targeting the main muscle groups, two to three sets, 6-12 repetitions, and avoiding free weights for safety reasons. The main results showed increments in strength, balance and fat-free mass and decrements in fat mass and waist circumference. It is a useful guideline for PE technicians to prescribe and adjust correctly in order to not only promote physical fitness, but improve the quality of life of individuals with ID.